2023
DOI: 10.3390/ecologies4020021
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Diversity Enhancement by Archaeological Structures: Bacterial Communities of an Historical Tannery Area of the City of Jena (Germany) Reflect the Ancient Human Impact

Abstract: Soil samples taken during archaeological investigations of a historical tannery area in the eastern suburb of the medieval city of Jena have been investigated by 16S r-RNA gene profiling. The analyses supplied a large spectrum of interesting bacteria, among them Patescibacteria, Methylomirabilota, Asgardarchaeota, Zixibacteria, Sideroxydans and Sulfurifustis. Samples taken from soil inside the residues of large vats show large differences in comparison to the environmental soil. The PCAs for different abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…For the evaluation of the results, the data from the saline samples from Bad Dürrenberg were compared with the data of the soil samples from the ancient coal mine exploration shaft near Bennstedt [12] also by PCA. The results of earlier studies on soil samples from human impact areas suggested the high importance of lower abundance bacterial types for distinguishing the character of local soil bacterial communities [37]. Therefore, here, the data of the saline samples of Bad Dürrenberg were analyzed together here with the samples from Bennstedt by a PCA distinguishing the abundance classes of single OTUs.…”
Section: General Sample Specificity Of Low Abundant Otus Shown By Com...mentioning
confidence: 99%
“…For the evaluation of the results, the data from the saline samples from Bad Dürrenberg were compared with the data of the soil samples from the ancient coal mine exploration shaft near Bennstedt [12] also by PCA. The results of earlier studies on soil samples from human impact areas suggested the high importance of lower abundance bacterial types for distinguishing the character of local soil bacterial communities [37]. Therefore, here, the data of the saline samples of Bad Dürrenberg were analyzed together here with the samples from Bennstedt by a PCA distinguishing the abundance classes of single OTUs.…”
Section: General Sample Specificity Of Low Abundant Otus Shown By Com...mentioning
confidence: 99%